National football promotion in China: Opportunities and challenges in public health - Xu, J.; Gao, C.; Zhao. J. (Journal of Sport and Health Science, 2016)
In 2015, a national reform plan was implemented by the central government that covers not only professional clubs and leagues but also campus and grassroots football, to develop football (soccer) in China. 1- According to the plan of China's Ministry of Education (MOE), 2-football will be nationally promoted among school students and youth. Furthermore, MOE plans to select 20,000 primary or middle schools in which the sport would have been promoted by 2020. Then, this number would be increased to 50,000 by 2025.